2014
DOI: 10.1007/s00420-014-0976-z
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of low back outcomes to internal spinal load: a prospective cohort study of professional drivers

Abstract: In this prospective cohort study, measures of internal spinal dose performed better than measures of daily vibration exposure (external dose) for the prediction of low back outcomes in professional drivers. The ISO boundary values of the risk factor R for low and high probabilities of adverse health effects on the lumbar spine tend to underestimate the health risk in professional drivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Our cross‐sectional study design limits our ability to draw firm conclusions about causality, since exposures and outcomes were measured at the same time. However, associations between our study's work exposures and health outcomes have been shown to be causally related in prospective studies 15,38–40 …”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Our cross‐sectional study design limits our ability to draw firm conclusions about causality, since exposures and outcomes were measured at the same time. However, associations between our study's work exposures and health outcomes have been shown to be causally related in prospective studies 15,38–40 …”
Section: Discussionmentioning
confidence: 75%
“…2112 13 . Recent studies also provide evidence that internal spinal load and WBV are risk factors for low back pain and sciatica 14,15 …”
Section: Introductionmentioning
confidence: 99%
“…More significantly, in a recent prospective study of 537 professional drivers [61], the occurrence of low back symptoms was related to internal forces caused by WBV and acting upon the spine. These were estimated from models that incorporated the static gravitational force acting on vertebral endplates, the vibration-related peaks of dynamic compression on vertebrae, individual characteristics of the drivers (e.g.…”
Section: Low Back Pain and Sciaticamentioning
confidence: 96%
“…Prevalence rate ratios (PR) and 95% confidence intervals (95% CI) were adjusted for age, smoking, and drinking habits, assuming the controls as the reference category [14]. Relationships of 7-day low back outcomes to daily compressive dose S ed and risk factor R in a three-year prospective cohort study of 537 professional drivers [61]. The changes in odds ratio (OR * ) and 95% confidence intervals (95% CI) for a change of 0.…”
Section: Research Agendamentioning
confidence: 99%
See 1 more Smart Citation